2014
DOI: 10.1530/joe-14-0356
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal exposure to bisphenol A exacerbates nonalcoholic steatohepatitis-like phenotype in male rat offspring fed on a high-fat diet

Abstract: Bisphenol A (BPA) is one of the environmental endocrine disrupting chemicals, which is present ubiquitously in daily life. Accumulating evidence indicates that exposure to BPA contributes to metabolic syndrome. In this study, we examined whether perinatal exposure to BPA predisposed offspring to fatty liver disease: the hepatic manifestation of metabolic syndrome. Wistar rats were exposed to 50 mg/kg per day BPA or corn oil throughout gestation and lactation by oral gavage. Offspring were fed a standard chow d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 47 publications
8
64
0
Order By: Relevance
“…Recently, a study was published using Wistar rats exposed prenatally to BPA at 50 μg/kg/day, and consuming a post-weaning HF diet. Male rats (female data were not shown) consuming a HF diet presented with BPA-induced hepatic steatosis at 27 weeks (Wei et al , 2014), and this was associated with a decrease in mitochondrial respiratory capacity and ATP production in the same model (Jiang et al , 2014). The study by Wei et al showed that in adult animals that had steatosis, Cpt1a was actually increased following developmental BPA exposures, and we also observed that BPA-exposed males in the current study had increased Cpt1a mRNA expression in adulthood (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a study was published using Wistar rats exposed prenatally to BPA at 50 μg/kg/day, and consuming a post-weaning HF diet. Male rats (female data were not shown) consuming a HF diet presented with BPA-induced hepatic steatosis at 27 weeks (Wei et al , 2014), and this was associated with a decrease in mitochondrial respiratory capacity and ATP production in the same model (Jiang et al , 2014). The study by Wei et al showed that in adult animals that had steatosis, Cpt1a was actually increased following developmental BPA exposures, and we also observed that BPA-exposed males in the current study had increased Cpt1a mRNA expression in adulthood (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…This dose has been shown to affect metabolism (including increased body weight and altered glucose homeostasis) and reproductive outcomes (including altered estrous cyclicity and hormone levels) in previous rodent models of perinatal exposure (Rubin et al , 2001; Liu et al , 2013). A relatively similar perinatal BPA exposure dose (50 μg/kg/day BW) led to steatosis in adult offspring (Jiang et al , 2014; Wei et al , 2014), and adult exposure to BPA at 50 and 500 μg/kg/day BW increased hepatic triglycerides in mice (Marmugi et al , 2012). Immediately after birth, litter sex distributions and offspring body weight were recorded, male and female pups (n=6, one of each sex from each dam) were removed for sampling, and the remainder of the pups were completely mixed within each treatment group, and 4 male and 4 female pups were randomly selected and placed back with each dam within the respective control or BPA-treated groups for cross-fostering.…”
Section: Methodsmentioning
confidence: 99%
“…Although our chosen animal models were C57BL/6 male mice fed with HFD, treatment with BPA has also consistently been shown to induce insulin resistance in various other animal models, such as male Swiss albino OF1 mice (Alonso-Magdalena et al 2006, Batista et al 2012, CD-1 mice, HFD wistar rats (Wei et al 2014), and Watanabe heritable hyperlipidemic rabbits (Fang et al 2015). Therefore, it is quite likely that treatment with BPA would also induce increased insulin resistance in other insulinresistant animal models, such as ob/ob or db/db mice.…”
Section: Discussionmentioning
confidence: 99%
“…Wei et al . have demonstrated that bisphenol A exposure during the perinatal period exacerbated non-alcoholic steatohepatitis-like phenotype in high-fat diet (HFD)–treated male rat offspring 24 . In another study, Boucher et al have found that polychlorinated biphenyls (PCB) interfere with the normal functioning of vital metabolic pathways in the liver and are associated with the development of NAFLD 25 .…”
Section: Introductionmentioning
confidence: 99%